Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3892/ijmm.2017.3194
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of microRNA-650 in the regulation of B-cell CLL/lymphoma 11B gene expression following transplantation: A novel mechanism behind the acute rejection of renal allografts

Abstract: Kidney transplantation is an effective final therapeutic procedure for patients with end-stage kidney failure. Although advanced immunosuppressive therapy is administered following transplantation, certain patients still suffer from acute allograft rejection. MicroRNAs (miRs) have a potential diagnostic and therapeutic value for acute renal allograft rejection; however, their underlying mechanism of action is largely unknown. In the present study, an increased level of miR-650 was identified to be associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…For example, Liu et al reported that downregulated miR-10b could mediate rejection of renal allografts through inhibiting BCL2L11 expression [ 2 ]. Jin et al decoded a novel mechanism between miR-650 and BCL11B for preventing rejection after kidney transplantation [ 3 ]. Based on the meta-analysis and F344-Lewis rat kidney transplantation model, Liang et al explored the diagnostic role and dynamic change of miR-155 in acute rejection [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Liu et al reported that downregulated miR-10b could mediate rejection of renal allografts through inhibiting BCL2L11 expression [ 2 ]. Jin et al decoded a novel mechanism between miR-650 and BCL11B for preventing rejection after kidney transplantation [ 3 ]. Based on the meta-analysis and F344-Lewis rat kidney transplantation model, Liang et al explored the diagnostic role and dynamic change of miR-155 in acute rejection [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous genes have been shown to be closely involved in apoptotic and proliferative cellular processes, which is interesting given the established links between apoptosis, vascular calcification and CVD 10 12 , 29 , 30 . HIVEP3 31 , EID2 32 , ETS1 33 , MRFAP1 34 , ZNF224 35 , BCL11B 36 , 37 , SKI 38 , 39 , ZMIZ1 40 , GFI1 41 , HDAC4 42 , MAD1L1 43 , NCOR2 44 , 45 , ANKRD11 46 , BANP 47 , and ARID3A 48 , 49 all have functions related to apoptosis, cell survival or cell cycle progression. This highlights the importance of cell cycle activity, apoptosis, and cellular senescence in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in microRNA therapeutics have shown the extensive use of microRNAs for cancer and infections ( Rupaimoole and Slack, 2017 ). There has been increased support for microRNA therapeutics in solid organ transplantation, including kidney ( Wilflingseder et al, 2015 ; Jin et al, 2017 ; Ledeganck et al, 2019 ), lung ( Benazzo et al, 2022 ), and heart transplantation ( Hamdorf et al, 2017 ). Candida albicans have been linked to cancerous processes by taking advantage of the compromised immune system ( Ramirez-Garcia et al, 2016 ; Chung et al, 2017 ; Sultan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%